1981
DOI: 10.1017/s0025315400045926
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive, genetic and ecological evidence thatActinia equinavar.mesembryanthemumand var.fragaceaare not conspecific

Abstract: The intertidal distributions of the two varieties of Actinia equina L. defined by Stephenson (1935), var mesembryanthemum and vai.fragacea, have been studied on several shores of the English Channel. The reproductive physiology and iso-enzyme genetics of sympatric populations of the two taxa have been investigated in greater detail on one shore. The genetic results show that the two taxa are reproductively isolated and, overall, the evidence indicates that they are separate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…by Harris and Hopkinson, 1978;Ferguson, 1980). Further information on procedures for Actinia is given by Carter and Thorpe (1981). Shandon electrophoresis equipment was used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…by Harris and Hopkinson, 1978;Ferguson, 1980). Further information on procedures for Actinia is given by Carter and Thorpe (1981). Shandon electrophoresis equipment was used.…”
Section: Methodsmentioning
confidence: 99%
“…This difference indicates, in our opinion, the probability that Odh in the green morph is qualitatively different from that of other Actinia (cf. Xod differences between A. equina and A. fragacea, Carter and Thorpe, 1981), although the possibility of a massive quantitative difference alone cannot be eliminated entirely. A qualitative difference would provide evidence for genetic differentiation of the green morphs, whilst a quantitative difference may not do so.…”
Section: Enzyme Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently the only taxonomic scheme in general use was that of Stephenson (1935) Thorpe (1981) other biochemical genetic studies have investigated the structure of gene pools in Actinia equina (e.g. Orr et al 1982, 1984) and in particular Haylor et al (1984) have shown that a certain green morph is reproductively isolated from other sympatrically occurring morphs of the species.…”
Section: Introductionmentioning
confidence: 99%